Horse stable environment: what to expect regarding fungi and particles occupational exposure? - Viegas, Carla (2015)
The simultaneous presence of fungi and particles in horse stable environment can create a singular exposure condition because particles have been reported has a good carrier for microorganisms and their metabolites. This study intends to characterize this setting and to recognize fungi and particles occupational exposure.